Digital value chain restructuring and labour process transformations in the fast-fashion sector: Evidence from the value chains of Zara & H&M - Tatiana López; Tim Riedler; Heiner Köhnen; Michael Fütterer (Global Networks, 2022)
In this article, we combine a workplace-centred Labour Process Theory approach with a multi-level Global Value Chain perspective to link digital labour process transformations in the fast-fashion value chain to broader dynamics of digital value chain restructuring. Drawing on a case study of H&M and Zara, we show how these retailers' digital supply chain management strategies are linked to the de-skilling, standardization and rationalization of tasks and to the emergence of new digital forms of labour control in production, logistics and retail. At the same time, we find that the effects of these transformations on working conditions are mediated by workers' position in the value chain as well as by gender and capital-labour power relations. The article contributes to debates on value chains and digitalization by revealing how, under digital capitalism, the ability to control and digitally integrate labour processes in complex store, logistics and manufacturing networks represents a key source of power in buyer-driven value chains.
Keywords: 320; digital Taylorism; digitalization; fast-fashion; global value chains; labour process; value chain restructuring